Paléoparasitologie : Apports des méthodes de la Parasitologie médicale à l’étude des populations anciennes - Stéphanie Harter; Françoise Bouchet (Bulletins et Mémoires de la Société d’Anthropologie de Paris, 2002)
Since the beginning of the 20th century, research into parasitic diseases has been carried out in the European and American scientific community. The application of the diagnostic methods of current medical coprology to increasingly varied archaeological samples has made it possible to augment the data for Palaeopathology by the discovery of other infectious diseases not before detected.